Interactions of alpha- and gamma-interferon in the transcriptional regulation of the gene encoding a guanylate-binding protein. - Decker, T (1989)
Transcriptional regulation of the gene encoding a guanylate-binding protein (GBP) by the two interferon (IFN) types was studied. GBP gene transcription was regulated by alpha IFN in a manner identical to that of previously described IFN-stimulated genes (ISGs): rapid induction, without a need for protein synthesis, followed by a protein synthesis-dependent suppression of transcription to basal levels within 6 h. Transcriptional induction by gamma IFN was equally rapid and independent of ongoing protein synthesis but remained at elevated levels for greater than 24 h. Experiments employing combined treatments with IFNs of both types revealed that induction of the GBP gene by gamma IFN overrides the alpha IFN-induced active repression and reverses the alpha IFN-induced repressed state. Moreover, the alpha IFN-mediated repression of ISG54, a gene normally responsive to only alpha IFN, is also reversed by gamma IFN. Induction of GBP by gamma IFN is presumably mediated by a factor different from the recently described activator Interferon Stimulated Gene Factor 3 (ISGF3) because induction of this factor was not observed upon treatment of cells with gamma IFN. Finally, a complex set of reinforcing or synergistic effects were observed when induction of the GBP gene was evoked by a combined treatment with the two IFN types.